Metode Pengukuran Potensi Energi Terbarukan: Upaya Meningkatkan Keterampilan Praktis dan Interpersonal Mahasiswa untuk Mendukung Inisiatif Konservasi dan Diversifikasi Energi - Muljono, Agung Budi; Nrartha, I Made Ari; Sultan, Sultan; Ginarsa, I Made; Natsir, Abdul; Tohri, M.; Yadnya, Made Sutha; Sasongko, Sudi Mariyanto Al (Universitas Mataram, 2024)
The importance of renewable energy use is increasing to support energy sustainability around the world and reduce the use of fossil resources that are increasingly limited. To achieve national energy security, it is necessary to regulate the development of renewable energy to all groups including students, must work together to encourage energy conservation and diversification programs. Based on this, training on the planning of new and renewable energy potential measurement methods was conducted to improve student skills in theory and implementation in the field of new and renewable energy. The methodology in this activity will involve a structured series of steps to measure renewable energy potential while improving students' practical skills and interpersonal skills. The evaluation of the training results in an increase in students' knowledge in applying their analytical skills to interpret the measurement results and calculate the potential energy that can be generated from the measured sources.